Towards maximising curriculum relevance : a cultural-historical analysis of partnership between technical and vocational education and training and industry - Junias, Kristofina (Stellenbosch : Stellenbosch University, 2023)

(untitled)
Thesis (PhD)--Stellenbosch University, 2023.